2002
DOI: 10.1046/j.1365-2168.2002.02117.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of axillary recurrence after conservative breast surgery

Abstract: Axillary recurrence is rare, although more common in younger women with large tumours. Radiotherapy to the breast was protective. Tumour size and node status were the most important prognostic factors in women with axillary recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…Oncological safety might, however, be compromised as port-site metastases occurred in two patients (4%), one of whom suffered concomitantly from an axillary recurrence (2%). Current medical literature describes a similar axillary recurrence rate between 0 and 2% after open ALND [22]. In the above mentioned study from our institution an axillary recurrence rate of 1.3% after standard ALND of level l and II was observed [10].…”
Section: Discussionmentioning
confidence: 78%
“…Oncological safety might, however, be compromised as port-site metastases occurred in two patients (4%), one of whom suffered concomitantly from an axillary recurrence (2%). Current medical literature describes a similar axillary recurrence rate between 0 and 2% after open ALND [22]. In the above mentioned study from our institution an axillary recurrence rate of 1.3% after standard ALND of level l and II was observed [10].…”
Section: Discussionmentioning
confidence: 78%
“…[30][31][32] On the other hand, axillary recurrence usually occurs after a median time of 24 months after surgery. 33,34 Of particular note is the randomized trial conducted by Naik et al 35 comparing the risk of axillary relapse after sentinel lymph node biopsy for breast cancer with axillary LR, according to which relapse ranged from 0% to 1.4% after 14-46 months of follow-up, with comparably good results (0.12% axillary recurrence rate) in patients with a negative SLNB and no ALND. Interestingly, Kingsmore et al 36 found recently that axillary recurrence was more than twice as likely after inadequate treatment of the axilla than after adequate treatment, despite endocrine therapy, chemotherapy, or radiotherapy (clearance 4%; sampling 10%; no procedure 13%).…”
Section: Discussionmentioning
confidence: 98%
“…Axillary lymph node status has been considered to be the most important independent prognostic factor, after primary tumor DOI 10.1080/02841850701305440 # 2007 Taylor & Francis status, for recurrence and survival (4,6). The procedure is fairly simple, but ALND is associated with considerable morbidity, including lymphedema of the arm, and numbness, stiffness, impaired shoulder movement, and pain (9).…”
mentioning
confidence: 99%